2015
DOI: 10.1590/0004-282x20150077
|View full text |Cite
|
Sign up to set email alerts
|

Combination of pharmacotherapy and lidocaine analgesic block of the peripheral trigeminal branches for trigeminal neuralgia: a pilot study

Abstract: Classical trigeminal neuralgia (CTN) is treated predominantly by pharmacotherapy but side effects and unsuccessful occurs. The current study was carried out to evaluate the therapeutic effect of combination of pharmacotherapy and lidocaine block. Thirteen patients with CTN managed with pharmacotherapy were recruited and assigned either to no additional treatment (Group I) or to additional analgesic block (Group II). The primary endpoint was the reduction in the frequency of pain episodes in a month assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Consistent with the literature, our study also showed that peripheral nerve injections were safe in terms of side effects and complications. [13][14][15][16] One of the limitations of our study is its retrospective design. Prospective randomized controlled studies with long-term follow-up may clarify the clinical efcacy of peripheral nerve blocks in trigeminal neuralgia and help to identify the factors realted with clinical success.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistent with the literature, our study also showed that peripheral nerve injections were safe in terms of side effects and complications. [13][14][15][16] One of the limitations of our study is its retrospective design. Prospective randomized controlled studies with long-term follow-up may clarify the clinical efcacy of peripheral nerve blocks in trigeminal neuralgia and help to identify the factors realted with clinical success.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results have been shown in the case series in which peripheral nerve blocks were evaluated in 3-9 patients with trigeminal neuralgia, consistent with the clinical efficacy that may extend up to 6 mo. [13][14][15] Stani et al [16] demonstrated that the combination of lidocaine injection for the peripheral branches of the trigeminal nerve with pharmacological therapy was superior to pharmacological therapy in the short term follow-up. Bainton et al showed a prolonged clinical response of peripheral nerve blocks was associated with neurotoxicity of local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…In only one randomized study, quality of life was investigated in 13 patients suffering from trigeminal pain 10 . Six patients received TNB using 2% lidocaine injected in the supra/infra orbitary or mandibular foramens.…”
Section: Discussionmentioning
confidence: 99%
“…This study only included 6 patients and did not show a substantial improvement in quality of life 30 and 90 days after performing the block. Moreover, quality of life was a secondary objective of this study 10 . The main objective of the present study was thus to evaluate the effect of TNB on the quality of life 15 days after TNB in patients suffering from trigeminal neuralgia refractory to classically recommended clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A peripheral nerve block with different local anesthetics may be beneficial for some TN patients [ 125 , 126 ]. More recently, it has been suggested that the association of peripheral nerve block with systemic TN pharmacotherapy may result in better pain control with reduced side effects, due to the possibility of lowering anticonvulsant doses [ 127 - 129 ]. Finally, a few studies have proposed the application of local anesthetic trough medicated plasters, intranasal sprays and epidural catheters [ 130 , 131 ].…”
Section: Treatmentmentioning
confidence: 99%